Effect of biofertilizer on growth and metaxylem diameter of Amaranthus tricolor L. in salinity stress condition - Okky Shavira Riesty; Dwi Umi Siswanti (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Throughout history, agricultural sector in Indonesia has faced a shortage of land. As a result, we must take use of land that is still available, even if the conditions are unsuitable for plant growth, one of which is salinity-stressed land. Amaranth is a frequently cultivated plant in Indonesia (Amaranthus tricolor L.). This vegetable plant is commonly consumed as food due to its nutritional content and numerous health benefits. To cultivate amaranth on salinity-stressed land, additional nutrients are required to ensure that the plants continue to thrive. One of them is the provision of biofertilizers, a type of organic fertilizer that contains beneficial bacteria for plant growth. This study aimed to determinate the effect of biofertilizer application on the growth and diameter of the stem metaxylem of amaranth plants growing in a salinity-stressed environment. As a salinity stress treatment, NaCl was applied at doses of 0, 2500, 5000, 7500, and 10000 ppm. The diameter of the metaxylem was determined by making fresh preparations across amaranth stems. The biofertilizer application does not affect the height and number of leaves of the plant. However, as the dose of biofertilizer was increased, the value of the metaxylem diameter of the stem increased.